The psychometric properties of three self-report screening instruments for identifying frail older people in the community - van Rossum Erik; Daniëls Ramon; Metzelthin Silke F; de Witte Luc; van den Heuvel Wim JA; Kempen Gertrudis IJM (BMC, 2010)
Abstract Background Frailty is highly prevalent in older people. Its serious adverse consequences, such as disability, are considered to be a public health problem. Therefore, disability prevention in community-dwelling frail older people is considered to be a priority for research and clinical practice in geriatric care. With regard to disability prevention, valid screening instruments are needed to identify frail older people in time. The aim of this study was to evaluate and compare the psychometric properties of three screening instruments: the Groningen Frailty Indicator (GFI), the Tilburg Frailty Indicator (TFI) and the Sherbrooke Postal Questionnaire (SPQ). For validation purposes the Groningen Activity Restriction Scale (GARS) was added. Methods A questionnaire was sent to 687 community-dwelling older people (≥ 70 years). Agreement between instruments, internal consistency, and construct validity of instruments were evaluated and compared. Results The response rate was 77%. Prevalence estimates of frailty ranged from 40% to 59%. The highest agreement was found between the GFI and the TFI (Cohen's kappa = 0.74). Cronbach's alpha for the GFI, the TFI and the SPQ was 0.73, 0.79 and 0.26, respectively. Scores on the three instruments correlated significantly with each other (GFI - TFI, r = 0.87; GFI - SPQ, r = 0.47; TFI - SPQ, r = 0.42) and with the GARS (GFI - GARS, r = 0.57; TFI - GARS, r = 0.61; SPQ - GARS, r = 0.46). The GFI and the TFI scores were, as expected, significantly related to age, sex, education and income. Conclusions The GFI and the TFI showed high internal consistency and construct validity in contrast to the SPQ. Based on these findings it is not yet possible to conclude whether the GFI or the TFI should be preferred; data on the predictive values of both instruments are needed. The SPQ seems less appropriate for postal screening of frailty among community-dwelling older people.